2012
DOI: 10.3109/00016357.2011.654261
|View full text |Cite
|
Sign up to set email alerts
|

Enamel properties after tooth bleaching with hydrogen/carbamide peroxides in association with a CPP-ACP paste

Abstract: The use of a CPP-ACP paste mixed to carbamide/hydrogen peroxides can decrease adverse side-effects from tooth bleaching on an enamel surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 20 publications
2
39
1
Order By: Relevance
“…The highest micro-roughness in conventional method was due to the high pH level of Kimia gel used in the process. The results of this study were in accordance with the studies of Pinto et al, 11 Dominguez et al, 12 De Vasconcelos et al, 13 and Sasaki et al, 14 which reported that in-office bleaching increases surface roughness of enamel. The results of the present study were in contrast with the results of McGuckin et al, 15 Mondelli et al 16 and Borges et al 17 which indicated that in conventional bleaching procedure, the enamel micro-roughness could not increase.…”
Section: Discussionsupporting
confidence: 92%
“…The highest micro-roughness in conventional method was due to the high pH level of Kimia gel used in the process. The results of this study were in accordance with the studies of Pinto et al, 11 Dominguez et al, 12 De Vasconcelos et al, 13 and Sasaki et al, 14 which reported that in-office bleaching increases surface roughness of enamel. The results of the present study were in contrast with the results of McGuckin et al, 15 Mondelli et al 16 and Borges et al 17 which indicated that in conventional bleaching procedure, the enamel micro-roughness could not increase.…”
Section: Discussionsupporting
confidence: 92%
“…Structural changes in the enamel have also been described with CP at low concentrations. [54][55][56][57][58] However, in this study, we observed no morphological changes, though a nonsignificant decrease in Ca and P was recorded with respect to the corresponding controls after both 14 hours of application (group CP14) and after 28 hours of treatment (group CP28). Some authors have obtained results similar to our own.…”
Section: Discussioncontrasting
confidence: 54%
“…As observed in the present investigation, some studies demonstrated that application of 16% CP gel also causes more intense morphological changes on enamel surface and reduction of enamel microhardness compared to lowconcentration CP-gels (10)(11)(12). On the other hand, other studies did not observe significant differences on dental enamel structure between bleached or non-bleached surfaces (21)(22)(23), and also among different concentrations of the CP-gels (23).…”
Section: Discussionmentioning
confidence: 33%
“…This way, since the higher CP concentration causes higher toxic effects in the pulp cells (3), more intense and prevalent tooth sensitivity (8,25), and higher modifications on the mineralized phase of teeth (10)(11)(12), with no benefits in the final esthetic outcome (14,15,25), the 10% CP gel appears to be an interesting alternative for tooth bleaching associated with less intense adverse events. However, based on the fact that data from in vitro study cannot be directly extrapolated to clinical situations, it is strongly recommended that further in vivo studies should be carried out to evaluate the effects of 16% CP gel on enamel, dentin and pulp tissue of patients subjected to tooth bleaching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation